Know When to Test: Optimizing Diagnostic Practices for Clostridium difficile Infection (CDI) Among Patients at a Tertiary-Care Cancer Center. (4th October 2017) - Aslam, Anoshé; Eagan, Janet; Kaplan, Janice; Robilotti, Elizabeth; McMillen, Tracy; Kamalska-Cyganik, Monika; Kelson, Suzanne; Nevrekar, Reshma; Narain, Wazim; Stetson, Peter; Kamboj, Mini; Babady, N Esther
Abstract: Background: Polymerase chain reaction (PCR) based diagnostic testing for the detection of toxigenic Clostridium difficile infection (CDI) does not distinguish between carriers and patients with true CDI. As a result, CDI is over-diagnosed in hospitalized patients with diarrhea. Unnecessary testing generates false positives and several downstream sequelae. Aim: The aim of this study was to reduce unnecessary testing for CDI through an electronic alert, targeted education, and implementation of evidence-based laboratory testing policy. Methods: In order to quickly identify laxative induced diarrhea and avoid CDI testing, an electronic alert was created in the electronic medical record (EMR) system. The alert was built on a logic that identified patients who had received laxatives within 48 hours of a CDI PCR test order. The alert additionally provided the rationale for avoiding testing in patients on laxatives and guidance on appropriate testing for CDI. The following steps were taken simultaneously to complement these efforts: 1) Infection Control conducted hospital-wide education for licensed independent practitioners on a CDI testing algorithm 2) Laboratory based policy was instated to reject all formed stools (Bristol Stool Chart types 1 through 4) for CDI testing. Results: In the 6 month pre-intervention period, there were 29 CDI tests per 1000 patient-days. In the post-intervention period, CDI tests decreased to 19 per 1000 patient-days, a 35% decrease ( P < 0.0001). The decline in testing has been sustained for 7 months. The following observations were also made: 1) HAI rate reduction of 28%; 2) decrease in oral vancomycin use. Conclusion: Decreasing inappropriate testing has several distinct advantages, including reducing excessive and unnecessary antibiotic use, avoiding misclassification of carriers as CDI cases, normalizing healthcare-associated CDI rates, and diminishing healthcare costs associated with preventable tests. Laboratories that use PCR only testing for CDI diagnosis should follow stringent policies to ensure that only patients with high pretest probability are tested. EMR systems are a useful and effective resource to achieve this for patients with laxative induced diarrhea. Disclosures: All authors: No reported disclosures.